MACROECONOMIC FACTORS AND REGULATORY QUALITY EFFECTS ON ASEAN-6 STOCK MARKET RETURNS - Mattualy, Stephany; Franse, Franse; Maichal, Maichal (Procuratio : Jurnal Ilmiah Manajemen, 2025)
This study examines the role of macroeconomic factors and regulatory quality on equity market performance in ASEAN-6 countries, namely Indonesia, Malaysia, Singapore, Thailand, Vietnam, and the Philippines, during 2006–2023. The objective is to identify the extent to which GDP growth, real interest rates, exchange rates, and regulatory quality affects stock market index growth. Secondary data from the World Bank, Investing.com, and official government institutions was used to conduct a quantitative analysis for this research. The analysis employs panel data regression with model specification tests, including the Chow and Hausman tests, to determine the appropriate estimation method. The results confirm that the Fixed Effect Model is the most suitable model. The findings show that GDP growth has a positive and statistically significant effect on stock market performance, while exchange rate depreciation has a significant negative impact. In contrast, real interest rates and regulatory quality are found to have no significant influence. The study concludes that macroeconomic fundamentals, particularly economic growth and exchange rate stability, are more decisive in driving stock market outcomes in ASEAN-6 compared to institutional quality. These results contribute valuable insights for policymakers and investors in managing risks and supporting sustainable capital market development. Penelitian ini mengkaji pengaruh faktor makroekonomi dan kualitas regulasi terhadap kinerja pasar saham pada negara ASEAN-6, diantaranya Indonesia, Malaysia, Singapura, Thailand, Vietnam, dan Filipina, selama periode 2006–2023. Penelitian ini dilakukan guna menganalisis sejauh mana pertumbuhan PDB, suku bunga riil, nilai tukar, dan kualitas regulasi mempengaruhi perkembangan indeks pasar saham. Melalui data sekunder dari World Bank, Investing.com, dan lembaga pemerintah resmi, pendekatan kuantitatif digunakan untuk melakukan penelitian ini. Analisis dilakukan dengan pendekatan regresi data panel serta uji spesifikasi model, termasuk uji Chow dan Hausman, untuk menentukan pendekatan estimasi yang sesuai. Hasil penelitian menunjukkan bahwa Fixed Effect Model adalah model yang paling sesuai. Temuan memperlihatkan bahwa pertumbuhan PDB berpengaruh positif dan signifikan terhadap kinerja pasar saham, sementara depresiasi nilai tukar berpengaruh negatif signifikan. Sebaliknya, suku bunga riil dan kualitas regulasi tidak berpengaruh signifikan. Penelitian ini menyimpulkan bahwa faktor fundamental makroekonomi, khususnya pertumbuhan ekonomi dan stabilitas nilai tukar, lebih berperan dalam mendorong kinerja pasar saham di ASEAN-6 dibandingkan kualitas institusional. Hasil ini memberikan masukan penting bagi pembuat kebijakan dan investor dalam mengelola risiko serta mendukung pengembangan pasar modal yang berkelanjutan.